Physicochemical characteristics of tropical jatrophacurcas seed oil (Sifat fizikokimia minyak biji Jatropha curcas Tropika) - Jumat Salimon; Waled Abdo Ahmed (Universiti Kebangsaan Malaysia, 2012)
The oil fraction of Jatropha curcas seeds from Malaysia, Indonesia and India were extracted by using cold press method. Their chemical and physical properties such as oil content, % water, specific gravity at 28oC, refractive index at 25oC, colour at 28oC, viscosity at 28oC, iodine value, acid value, triacylglycerol (TAG) composition, free fatty acid, saponification, and unsaponifiable value were examined. The results showed that the Malaysian seed sample contained high oil percentage, 33.7%. On the other hand, the oil content from Indonesian and Indian seeds were 32.7% and 30.5%, respectively. The physicochemical properties showed iodine value of 103.2, 99.8 and 97.9, acid value of 2.4, 9.9 and 7.6, FFA% of 1.68%, 6.99% and 5.35%, saponification value of 197.8, 183.2 and 156.2 and unsaponifiable value of 1.99%, 2.15% and 2.35% for Malaysian, Indonesian and Indian crude oil respectively. Although, the percentage of the TAGs and fatty acids of tropical Jatropha curcas oil were different, both oleic (43.5%-43.8%) and linoleic (33.1%-34.7%) acids were detected as the dominant unsaturated fatty acids, while palmitic (14.7%-14.9%) and stearic (7.0%-7.2%) acids were the saturated fatty acids found in the oil. Unlike most Jatropha curcas oils, tropical Jatropha curcas oil also contained palmitolic acid (0.8%) as part of minor fatty acids in the oil. Polyunsaturated TAGSs of PLL, OOL and OLL were the major TAGs found in the tropical Jatropha curcas oil.